Conference Report: Second World Conference on Nanomedicine and Drug Delivery. (June 2011) - Ninan, Neethu; Thomas, Sabu; George, Anne; Sebastian, Mathew
The Institute of Holistic Medical Sciences (IHMS, Kottayam, Kerala, India); the Institute of Macromolecular Science and Engineering (IMSE, Kottayam, Kerala, India) and Mathew Ayurveda und Venen Klinik (MUVK, Klegenfurt, Austria) have jointly conducted a 3-day world conference on Nanomedicine and Drug Delivery (WCN 2011) in Kottayam, Kerala, India from 11–13 March 2011. Application of nanotechnology for treatment, diagnosis, monitoring and control of biological systems has been referred to as 'nanomedicine'' by the NIH. Research into the rational delivery and targeting of pharmaceutical, therapeutic, and diagnostic agents is at the forefront of projects in nanomedicine. Nanotechnology will also provide devices to examine tissues in minute detail. Biosensors that are smaller than a cell would give us an inside look at cellular function. Tissues could be analyzed down to the molecular level, giving a completely detailed 'snapshot'' of cellular, subcellular, and molecular activities. Today, nanotechnology and nanoscience approaches to particle design and formulation are beginning to expand the market for many drugs and are forming the basis for a highly profitable niche within the industry, but some predicted benefits are hyped. This article gives an outlook of the ongoing research projects conducted all over the world, presented at the conference that highlight rational approaches in design and surface engineering of nanoscale vehicles and entities for site-specific drug delivery and medical imaging after parenteral administration. Potential pitfalls or side effects associated with nanoparticles were also discussed.